A social realist analysis of collaborative curriculum development processes in an academic department at a South African university - Vorster, Jo-Anne (Rhodes University, Faculty of Humanities, Department of Sociology, 2010)
This study reports on a social-realist analysis of collaborative curriculum development in a journalism and media studies (JMS) department at a South African university. Archer's social-realist meta-theoretical framework is used to theorise about mechanisms that influence collaborative curriculum development within the context of the JMS Department. The thesis examines the cultural, structural and agential conditions that influenced the process of developing a JMS curriculum that aimed to integrate theory and practice. Bernstein's theories of knowledge recontextualisation and disciplinary knowledge structures are used in the analysis. Bernstein argues that knowledge recontextualisation constitutes a site of struggle. This thesis is an examination of the "struggles" for the epistemic-pedagogic device (Maton's elaboration of Bernstein's epistemic device) during the recontextualisation process that aimed to integrate media studies (MS) and media production (MP) in the JMS curriculum. Traditionally academic work has been an individual endeavour. However, given the growing need to work in disciplinary and inter-disciplinary teams, it is imperative to develop knowledge of the mechanisms that influence such practices. This thesis is a contribution to knowledge of collaborative processes at the level of an academic department in a university. It contributes to knowledge of cultural, structural and agential mechanisms that enable or constrain collaborative curriculum development within a particular kind of context. In addition it contributes to knowledge of the nature of leadership that may be necessary to facilitate productive collaborative relationships and practices in such a context. The curriculum development project reported on in this thesis was initiated in 2003; however, data collection for the study was conducted in 2006 when the curriculum for the fourth year (JMS 4) of the Bachelor of Journalism degree was developed. Since the JMS course prepares students to work as journalists or media workers it is necessary for the curriculum and pedagogy to be oriented both towards the academy and towards the media industries. The aim of the JMS degree is to develop students who will be critically reflexive journalists or media workers. As such the course is both theoretical (MS) and practical (MP). One of the findings of this research project is that the integration of MS and MP is a complex project given that the knowledge of the two disciplines is structured differently. MS is concept-dependent and some aspects of it can be applied to journalism and media practice, while MP is practical and thus context-dependent, though underpinned by theory. A further finding is that both the collaborative work and the integration project required different identity shifts from the lecturers in the JMS Department. Some were more able to make the shifts than others. The thesis shows that the knowledge recontextualisation struggles in the curriculum development processes of the Department of JMS centred around, inter alia, the setting of boundaries between the department and the media and journalism industries, between MS and MP and between MS theory and journalism theory. In addition, existing boundaries between MS and MP lecturers had to be traversed. These boundaries were circumscribed by, amongst other things, unequal power relations emanating from the higher status traditionally accorded to theoretical knowledge by universities, the tensions around the nature of journalism education and training and the differential properties and powers of the various lecturers within the department. The existence of a strong regulative discourse was found to be an important unifying mechanism in a tension-ridden context.
Keywords: Rhodes University -- Curricula; Journalism -- Study and teaching -- South Africa -- Grahamstown; Curriculum planning -- South Africa -- Grahamstown